Analisis Model Pembelajaran Induktif Kata Bergambar Dalam Mengatasi Kesulitan Menulis Permulaan Kelas II SD Negeri 01 Lubai Ulu - Artia, Winki; Jayanti, Jayanti; Kuswidyanarko, Arief (ANTHOR: Education and Learning Journal, 2023)
The purpose of this study was to see the results of the initial writing analysis of the secondgrade students of SD Negeri 01 Lubai Ulu. The method used is descriptive qualitative. The objects and informants in this study were second-grade elementary school students and second-grade elementary school teachers. The results of the preliminary writing research are divided into 5 categories, namely very good category, good category, sufficient category, poor category, and very poor category. Students who have a very good category are 17 students or 80.95%, students who have a good category are 1 student or 4.76%, and students who have a sufficient category are 3 students or 14.28%. and there are no students who have poor and very poor categories. The average value of students' initial writing using the picture word inductive learning model in second-grade elementary school students is 92.85% or is included in the very good category. So it can be concluded that the Picture Word Inductive Learning Model can overcome this initial writing difficulty as evidenced by the student test results using the Picture Word Inductive Learning Model. It is hoped that during the learning process, the teacher can create a pleasant learning atmosphere and involve the activities of all students.